Electroimmunoblotting of myelin basic protein peptides: a novel approach to the rapid characterisation of antigenic specificities of monoclonal and polyclonal anti-MBP antibodies - Sheng, H.Z.; Martenson, R.E.; Grgacic, E.V.; Dowse, Carol; Carnegie, R.L.; Bernard, C.C.A. (Elsevier, 1988)
A rapid and sensitive method for the identification of antigenic determinants recognised by monoclonal and polyclonal antibodies directed against myelin basic protein (MBP) is described. By electroimmunoblotting a series of overlapping peptides covering the entire MBP molecule with monoclonal anti-MBP antibodies, the binding pattern of immunoreactive peptides can be rapidly determined and the reactive antigenic determinant identified. This procedure, which can be performed with both native and synthetic peptides, can also with appropriate modification, be applied to the analysis of naturally occuring or experimentally induced polyclonal anti-MBP autoantibodies. © 1988.